Perancangan Dan Implementasi Media Pembelajaran Gerbang Logika Berbasis Augmented Reality Menggunakan Standar ISO 25010 - Ombai, Taufiq Ombai; Putri, Putri Mandarani; Eko, Eko Kurniawanto Putra; Anna, Anna Syahrani; Anisya, Anisya (Pusat Riset dan Inovasi Nasional, 2024)
This research discusses the use of Augmented Reality (AR) based learning media with the aim of building learning applications in the field of Digital Electronics Engineering with a focus on the topic of Logic Gates. The application was built using the Software Development Life Cycle (SDLC) method which refers to the ISO 25010 standard to ensure the quality and desirability of the application. The application has gone through a series of tests which include evaluation of 5 (five) different aspects, namely Functional Suitability, Performance Efficiency, Usability, Compatibility and Portability. The test results show that the application has an average response time of around 00.03.26 seconds in displaying AR objects. In addition, the app achieved a usability rate of 80% for users who had never studied the material before, so it can be classified as 'Fine'. Positive evaluation results on the usability aspect show that this application has the potential to improve the learning experience for users who do not have prior knowledge of the material.